PENERAPAN LANGKAH POLYA DALAM MENENTUKAN JARAK ANTARA DUA GARIS LURUS G1 DAN G2 (CENDEKIA: JURNAL ILMIAH PENDIDIKAN, 2019)
The purpose of this research is to describe the implementation of Polya phase that can improve student learning outcomes in solving word problems a matter of geometry  about determine the distance between two straight lines g1 and g2 Semester IV Mathematics Education Study Program STKIP Paris Barantai Kotabaru. This type of research is a classroom action Data collection techniques that were presented in this study. Based on the result of the research learning to use Polya phase can increase the studentâ€™s learning outcomes to solving the word problem about determine the distance between two straight lines g1 and g2 Semester IV Mathematics Education Study Program STKIP Paris Barantai Kotabaru, those are: 1) understanding the proble; 2) devising plan, 3) carrying out the plan;and 4) looking back at a complete solution. Key words : Polya Phase; Learning Outcomes; Word Problem; Distance of two lines.